1994
DOI: 10.1161/01.atv.14.10.1625
|View full text |Cite
|
Sign up to set email alerts
|

Body iron stores and presence of carotid atherosclerosis. Results from the Bruneck Study.

Abstract: We hypothesized that the formation of foam cells and fatty streaks requires a postsecretory oxidative modification of lipoproteins that targets them for rapid uptake by macrophages. Lipid peroxidation may in part depend on the concentration of tissue iron, one of the major oxidants in vivo. We analyzed the relation between sonographically assessed carotid atherosclerosis and body iron stores in a population sample of 847 men and women aged 40 to 79 years. In a logistic regression analysis adjusting for age, se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
146
1
4

Year Published

1996
1996
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(155 citation statements)
references
References 33 publications
4
146
1
4
Order By: Relevance
“…Subjects with inflammatory, neoplastic, and autoimmune diseases (nϭ85) were identified by an extensive clinical and laboratory screening as described elsewhere. 23 …”
Section: Clinical History and Examinationmentioning
confidence: 99%
“…Subjects with inflammatory, neoplastic, and autoimmune diseases (nϭ85) were identified by an extensive clinical and laboratory screening as described elsewhere. 23 …”
Section: Clinical History and Examinationmentioning
confidence: 99%
“…1,2 However, the relationship between iron status and atherosclerotic disease remains controversial. [3][4][5][6][7][8] Body iron metabolism is, at least in part, genetically influenced, and the recent identification of the gene for hereditary haemochromatosis (HH) on chromosome 6 has significantly improved our understanding of the molecular basis of iron metabolism. 9 HH is an autosomal recessive disease that leads to progressive tissue iron accumulation and multiorgan dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on humans revealed that increased serum ferritin, which reflects the level of total body iron stores, was found to be associated with increased risk of carotid atherosclerosis [18] and acute myocardial infarction [42]. Pang et al (1996) reported higher expression of L-ferritin and Hferritin mRNA (10 folds) and protein in human release of inflammatory mediators [29,47] Inflammation is known to accelerate vessel dysfunction and aging [20].…”
Section: Discussionmentioning
confidence: 99%
“…Also, ferritin gene expression was found to be increased in other cases, including cell proliferation, differentiation, inflammation, and specific hormonal signals. [18].…”
mentioning
confidence: 99%